Pengaruh Kerjasama Tim, Keterampilan Kerja, Dan Sikap Kerja Terhadap Produktivitas Kerja (Studi Kasus Pada PT. Colombo Kudus) - Maharani, Icha; Indiworo, Hawik Ervina; Dharmaputra, Fadjar (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2025)
Based on risearch. Found by researcersh, the company’s lack of teamwork has seen its target decrease. The target set by the company is 80.32% and there are other problems, apart from teamwork, there are also work skills and work attitudes, if they get worse it also affecs employee productivity. Therefore, how important teamwork, work skills and work attitudes are employee productivity at PT. Colombo Kudus. This research is included in the type of Quantitative research. Quantitative research uses quantitative data. quantitative data shows the amount or quantity of sometings. The sampling technique for determining a sample when all members of the population are used as samples. The sampling technique was carried out by distributing questionnaires and all employees in the population had the opportunity to file out the questionaires. Questionaires will be distributed at PT. Colombo Kudus production section. In this research, the population. For data analysis tecniques use SPSS. The test result show that te significant value of the teamwork variable on work productivity is 0.493>0.05 and the Tcount value is 0.687<1.975 Ttable. So it cant be that the concluded that the teamwork variable has no effet on work productivity. And it is known that the significant value of the work skills variable on work productivity 0.672>0.05 and the T value is 0.0424<1,975 Ttable. So it can be concluded that the work skils variable has no effect on work productivity. Menwhile, it is known that the significant variable work attitude towards work productivity is 0.000<0.05 and the T value is 4.117>1.975 Ttable. So it can be concluded that the work attitude variable on work productivity has positive and significant effect on work productivity.